Analysis of the administration distrital of supply in last two years (2014)
Through this work seeks to reflect, analyze, study, evaluate the work and contribution played by the capital management district for the welfare of the school population, in order to reduce the dropout rate of children and adolescents ; Delve into one of the main causes that causes dropouts, this being the school feeding component. Then, through intensive research, the mechanisms used by management to reduce this serious problem, which also affects the quality of life of childhood community in our country, noting the achievements, progress and has resulted in benefits was identified brought in years